The dynamics of US capitalism : corporate structure, inflation, credit, gold and the dollar - Sweezy, Paul M.; Magdoff, Harry (New York : Monthly Review Press, 1972)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: kapitalisme; Verenigde Staten